Positive electrode for lithium secondary battery and lithium secondary battery containing the same
By introducing a positive electrode additive with a needle-like crack structure into the positive electrode mixture layer of the lithium secondary battery, the side reactions and gas generation problems caused by irreversible additives are solved, and the safety and electrical performance of the lithium secondary battery are significantly improved.
Patent Information
- Application Number
- CN202280005844.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-02-09
- Filing Date
- 2022-04-05
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2042-04-05
AI Technical Summary
In existing lithium secondary batteries, the side reactions caused by irreversible additives and the amount of gas (such as oxygen) generated during charging/discharging is too large, resulting in deterioration of battery performance and reduced safety.
A positive electrode for a lithium secondary battery is designed, and the positive electrode mixture layer includes a first region of a dense structure and a second region of a needle-like crack structure inside and outside the second metal oxide particles after initial charging. The positive electrode additive is represented by the formula LipCo(1-q)M1qO4, M1 is a specific element, and p and q are values within a specific range.
By reducing the amount of gas generated by irreversible additives and improving the migration path of lithium ions and electrons, the battery safety and electrical performance of lithium secondary batteries are significantly improved.
Smart Images

Figure CN116057736B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a positive electrode for a lithium secondary battery and a lithium secondary battery including the positive electrode.
[0002] This application claims priority to and the benefit of Korean Patent Application No. 10-2021-0064296, filed on May 18, 2021, and Korean Patent Application No. 10-2022-0016953, filed on February 9, 2022, the disclosures of which are incorporated herein by reference in their entireties. Background Art
[0003] With the technological development and increasing demand for mobile devices, the demand for secondary batteries as energy sources is rapidly increasing. Among these secondary batteries, lithium secondary batteries with high energy density, high working potential, long cycle life and low self-discharge rate have been widely studied, commercialized and used in various fields.
[0004] Recently, with the use of lithium secondary batteries as power sources for medium and large devices such as electric vehicles, there is a further need for high-capacity, high-energy-density and low-cost lithium secondary batteries, and irreversible additives for electrodes are also required to have higher irreversible capacity. However, there are indeed limitations in developing positive electrode additives with such high irreversible capacity.
[0005] On the other hand, conventional irreversible additives such as Li6CoO4 are usually prepared by reacting excess metal oxides such as lithium oxide and cobalt oxide. The irreversible additives prepared as described above are structurally unstable and produce a large amount of oxygen (O2) as charging proceeds, and in the initial charging of the secondary battery, that is, in the activation of the battery, when the irreversible additive is not completely reacted and remains, it may react in the subsequent charge / discharge process, causing side reactions in the battery or producing a large amount of oxygen. The oxygen generated as described above may cause the volume expansion of the electrode assembly, becoming one of the main factors causing the degradation of battery performance.
[0006]
[0007] In addition, in the preparation of the slurry composition for electrode preparation, byproducts such as lithium oxide may react with the binder component, causing the viscosity of the composition to increase or gel. As a result, it is difficult to uniformly apply the electrode composition for forming the active material layer, and the characteristics of the battery are reduced.
[0008] Therefore, in order to improve the safety and electrical performance of lithium secondary batteries, it is necessary to develop a technology capable of reducing side reactions caused by irreversible additives or generation of gas such as oxygen (O 2 ) during charge / discharge.
[0009] [Related technical documents]
[0010] [Patent document]
[0011] Korean Unexamined Patent Application Publication No. 10-2019-0078392 Summary of the invention
[0012] Technical issues
[0013] Therefore, the present invention aims to provide a positive electrode for a lithium secondary battery and a lithium secondary battery, which can reduce the amount of side reactions caused by irreversible additives and gases such as oxygen (O2) generated during charging / discharging, thereby achieving excellent battery safety and high charging / discharging capacity.
[0014] Technical Solution
[0015] In order to solve the above problems, one aspect of the present invention provides a positive electrode for a lithium secondary battery, the positive electrode comprising:
[0016] a positive electrode current collector; and
[0017] A positive electrode mixture layer is provided on at least one surface of the positive electrode current collector and includes a positive electrode active material and a positive electrode additive represented by the following Formula 1,
[0018] Wherein, after initial charging, the cross-sectional structure of the positive electrode mixture layer comprises:
[0019] a first region having a dense structure filled with first metal oxide particles, and
[0020] a second region having a needle-like crack structure inside and outside the second metal oxide particle,
[0021] [Formula 1]
[0022] Li p Co (1-q) M 1 q O4
[0023] In formula 1,
[0024] M 1 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, and
[0025] p and q are 5≤p≤7 and 0≤q≤0.5 respectively.
[0026] Here, the second region may have a structure dispersed in the first region in an island shape.
[0027] Furthermore, the second region may occupy 0.001% to 10% of the total cross-sectional area of the positive electrode mixture layer.
[0028] Furthermore, the needle-like crack structure included in the second region may have cracks having an average thickness of 5 nm to 800 nm and an average length of 50 nm to 10 μm.
[0029] In addition, the positive electrode additive may have a tetragonal structure with a space group of P42 / nmc.
[0030] In addition, the positive electrode active material may be a lithium metal composite oxide represented by the following Formula 2:
[0031] [Formula 2]
[0032] Li x [Ni y Co z Mn w M 2 v ]O u
[0033] In formula 2,
[0034] M 2 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, and
[0035] x, y, z, w, v and u are 1.0≤x≤1.30, 0.1≤y<0.95, 0.01 respectively <z≤0.5、0.01<w≤0.5、0≤v≤0.2、1.5≤u≤4.5。
[0036] In addition, the positive electrode mixture layer may further include one or more conductive materials selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, and carbon fiber.
[0037] Another aspect of the present invention provides a lithium secondary battery, the battery comprising the positive electrode of the present invention, a negative electrode, and a separator disposed between the positive electrode and the negative electrode.
[0038] Here, the negative electrode may include a negative electrode current collector; and a negative electrode mixture layer provided on at least one surface of the negative electrode current collector and containing a negative electrode active material.
[0039] In addition, the negative electrode active material may contain a carbon material and a silicon material, and the carbon material may include one or more selected from the following: natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, graphene and carbon nanotubes, and the silicon material may include silicon (Si) particles and silicon oxide (SiO X , 1≤X≤2) particles.
[0040] In addition, the content of the silicon material may be 1 part by weight to 20 parts by weight relative to 100 parts by weight of the negative electrode mixture layer.
[0041] Beneficial Effects
[0042] The positive electrode for lithium secondary battery according to the present invention contains a positive electrode additive represented by Formula 1 in the positive electrode mixture layer, and after initial charging (activation), there is a region in the cross section of the positive electrode mixture layer: the region has a needle-like crack structure, thereby reducing the amount of gas such as oxygen generated by the irreversible additive as a positive electrode additive during subsequent charging / discharging, and ensuring the migration path of lithium ions and / or electrons. Therefore, it shows an excellent effect of improving the battery safety and electrical performance of the lithium secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 (a) and 1(b) are a set of scanning electron microscope (SEM) images showing the cross-sectional structure of the positive electrode for a lithium secondary battery according to the present invention before and after initial charge (activation), wherein:
[0044] Figure 1 (a) is the cross-sectional structure before initial charging (activation),
[0045] Figure 1 (b) is the cross-sectional structure after initial charging (activation). DETAILED DESCRIPTION
[0046] The present invention is susceptible to various variations and embodiments, and therefore specific embodiments are shown in the drawings and described in detail in the detailed description.
[0047] However, it should be understood that the present invention is not limited to the specific embodiments and includes all modifications, equivalents or substitutes within the spirit and technical scope of the present invention.
[0048] The terms "comprise", "include" and "have" used in this document indicate the presence of the features, quantities, steps, operations, components, members or combinations thereof described in this specification, but it should be understood that these terms do not exclude the possibility of the presence or addition of one or more other features, quantities, steps, operations, components, members or combinations thereof.
[0049] Furthermore, when a portion of a layer, film, region, or plate is disposed “on” another portion, this includes not only a case where one portion is “directly” disposed “on” another portion, but also a case where another portion is still interposed therebetween. Conversely, when a portion of a layer, film, region, or plate is disposed “under” another portion, this includes not only a case where one portion is “directly” disposed “under” another portion, but also a case where another portion is still interposed therebetween. Furthermore, in the present application, “on…” may include not only a case where it is disposed on an upper portion, but also a case where it is disposed on a lower portion.
[0050] In addition, the "main component" used in this article can be a component with a content of 50 weight% or more, 60 weight% or more, 70 weight% or more, 80 weight% or more, 90 weight% or more, 95 weight% or more, or 97.5 weight% or more relative to the total weight of the composition or a specific component. In some cases, when the main component constitutes the entire composition or a specific component, the content of the main component can be 100 weight%.
[0051] In addition, "Ah" used in this article refers to the capacity unit of lithium secondary batteries, also known as "ampere hours", which refers to the amount of current per hour. For example, when the battery capacity is "3000mAh", this means that the battery can discharge at a current of 3000mA for 1 hour.
[0052] Hereinafter, the present invention will be described in further detail.
[0053] Positive electrode for lithium secondary battery
[0054] In one embodiment of the present invention, the positive electrode for a lithium secondary battery comprises:
[0055] a positive electrode current collector, and
[0056] A positive electrode mixture layer is provided on at least one surface of the positive electrode current collector and includes a positive electrode active material and a positive electrode additive represented by the following Formula 1,
[0057] Wherein, after initial charging, the cross-sectional structure of the positive electrode mixture layer comprises:
[0058] a first region having a dense structure filled with first metal oxide particles, and
[0059] a second region having a needle-like crack structure inside and outside the second metal oxide particle,
[0060] [Formula 1]
[0061] Li p Co (1-q) M 1q O4
[0062] In formula 1,
[0063] M 1 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, and
[0064] p and q are 5≤p≤7 and 0≤q≤0.5 respectively.
[0065] The positive electrode for a lithium secondary battery according to the present invention has a structure in which a mixture layer is provided on a positive electrode current collector, wherein the positive electrode mixture layer has a configuration including a positive electrode active material and a positive electrode additive.
[0066] Here, the positive electrode active material may be a lithium composite transition metal oxide containing two or more elements selected from the group consisting of nickel (Ni), cobalt (Co), manganese (Mn), aluminum (Al), zinc (Zn), titanium (Ti), magnesium (Mg), chromium (Cr) and zirconium (Zr). For example, the positive electrode active material may be a lithium metal composite oxide represented by Formula 2 that can be reversibly intercalated and deintercalated:
[0067] [Formula 2]
[0068] Li x [Ni y Co z Mn w M 2 v ]O u
[0069] In formula 2,
[0070] M 2 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, and
[0071] x, y, z, w, v and u are 1.0≤x≤1.30, 0.1≤y<0.95, 0.01 respectively <z≤0.5、0.01<w≤0.5、0≤v≤0.2、1.5≤u≤4.5。
[0072] The lithium metal composite oxide represented by Formula 2 is a metal oxide containing lithium, nickel, cobalt and manganese, and in some cases, may be doped with different transition metals (M 2) form. For example, the positive electrode active material may include one or more compounds selected from the following: LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.9 Co 0.05 Mn 0.05 O2、LiNi 0.8 Co 0.1 Mn 0.05 Al 0.05 O2 and LiNi 0.7 Co 0.1 Mn 0.1 Al 0.1 As an example, in the positive electrode active material, as the lithium metal composite oxide represented by Formula 2, LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.8 Co 0.1 Mn 0.05 Al 0.05 O2 or LiNi 0.7 Co 0.1 Mn 0.1 Al 0.1 O2.
[0073] In addition, the content of the positive electrode active material may be 85 to 95 parts by weight, specifically 88 to 95 parts by weight, 90 to 95 parts by weight, 86 to 90 parts by weight, or 92 to 95 parts by weight, relative to 100 parts by weight of the positive electrode mixture layer.
[0074] In addition, the positive electrode mixture layer may include a positive electrode additive imparting irreversible capacity, and a positive electrode active material exhibiting electrical activity, wherein the positive electrode additive may include lithium cobalt oxide represented by the following Formula 1:
[0075] [Formula 1]
[0076] Li p Co (1-q) M 1 q O4
[0077] In formula 1,
[0078] M 1is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, and
[0079] p and q are 5≤p≤7 and 0≤q≤0.5 respectively.
[0080] The positive electrode additive may contain an excess amount of lithium to provide lithium for lithium consumption caused by irreversible, chemical and physical reactions at the negative electrode at the time of initial charge, ie, at the time of activation, thereby increasing the charge capacity, reducing the irreversible capacity, and improving the life characteristics.
[0081] Among them, the positive electrode additive represented by Formula 1 may have a higher lithium ion content than the nickel-containing oxide commonly used in the art, so it can replenish the lithium ions lost by irreversible reactions during the initial charge (activation) of the battery, so it can significantly improve the charge / discharge capacity of the battery. In addition, compared with the iron-containing oxides and / or manganese-containing oxides commonly used in the art, there is no side reaction caused by the dissolution of transition metals during the charge / discharge of the battery, so it exhibits excellent battery stability. Examples of lithium cobalt oxides represented by Formula 1 may include Li6CoO4, Li6Co 0.5 Zn 0.5 O4 and Li6Co 0.7 Zn 0.3 O4.
[0082] In addition, the average particle size of the lithium cobalt oxide represented by Formula 1 can be 0.1 to 10 μm, specifically 0.1 to 8 μm; 0.1 to 5 μm; 0.1 to 3 μm; 0.5 to 2 μm; 0.1 to 0.9 μm; 0.1 to 0.5 μm; 0.6 to 0.9 μm; 1 to 4 μm; 1.5 to 3.5 μm; 4 to 6 μm; 5 to 10 μm; or 6 to 9 μm. Since the average particle size of the lithium cobalt oxide of the present invention is controlled within the above range, the irreversible activity of the lithium cobalt oxide can be increased, and the powder conductivity of the lithium cobalt oxide can be prevented from decreasing.
[0083] In addition, relative to 100 parts by weight of the positive electrode mixture layer, the content of the positive electrode additive can be 0.01 to 5 parts by weight, specifically 0.01 to 4 parts by weight; 0.01 to 3 parts by weight; 0.01 to 2 parts by weight; 0.1 to 1 parts by weight; 0.5 to 2 parts by weight; 1 to 3 parts by weight; 2 to 4 parts by weight; 1.5 to 3.5 parts by weight; 0.5 to 1.5 parts by weight; 1 to 2 parts by weight; 0.1 to 0.9 parts by weight; or 0.3 to 1.2 parts by weight.
[0084] In addition, the lithium cobalt oxide represented by Formula 1 may have a tetragonal crystal structure, wherein it may be contained in a space group of P42 / nmc having a distorted tetragonal structure of cobalt and oxygen elements. Since the positive electrode additive having a distorted tetragonal structure has a distorted tetragonal structure composed of cobalt elements and oxygen elements and is therefore structurally unstable, side reactions and / or a large amount of oxygen may be generated in the battery during charge / discharge and initial charge / discharge. However, in the present invention, by partially introducing a region having a needle-like crack structure into the positive electrode mixture layer during initial charge (activation), the amount of gas such as oxygen generated by an irreversible additive as a positive electrode additive can be reduced, and the migration path of lithium ions and / or electrons can be ensured, thereby improving the battery safety and electrical performance of the lithium secondary battery.
[0085] Specifically, in the positive electrode for a lithium secondary battery according to the present invention, after initial charging (activation), the cross-sectional structure of the positive electrode mixture layer may include a first region having a dense structure filled with first metal oxide particles and a second region having a needle-like crack structure inside and outside the second metal oxide particles. More specifically, the first region refers to a region containing a lithium metal composite oxide represented by Formula 2 as a first metal oxide. Since the first metal oxide can be reversibly embedded and deintercalated during the charge / discharge of the lithium secondary battery, the charge / discharge of the lithium secondary battery does not cause lithium loss in the first metal oxide contained in the region, and in some cases, even when lithium loss occurs, it can be ignored. Therefore, it is observed by SEM that the first region can be densely filled with the first metal oxide particles without any cracks, or in some cases, a dense structure containing inconspicuous cracks less than 5nm is observed. The second region refers to a region composed of lithium cobalt oxide of Formula 1 as a second metal oxide. Since the second metal oxide has lithium loss by an irreversible electrochemical reaction during the initial charge of the lithium secondary battery, the second metal oxide contained in the region causes loss by the charge / discharge of the lithium secondary battery. Therefore, the second region may have a structure in which needle-shaped cracks are formed by lithium loss at the following locations: inside and outside of a plurality of densely packed second metal oxide particles (specifically, inside and on the surface of the second metal oxide particles); or at the interface between the second metal oxide particles.
[0086] In addition, the first region and the second region may constitute the positive electrode mixture layer, and the first region may serve as a continuous phase, so that the second region as a dispersed phase may have a structure uniformly dispersed in the first region as an island shape. In this case, the area ratio of the second region may account for 0.001% to 10% of the total cross-sectional area of the positive electrode mixture layer, more specifically 0.001% to 8%; 0.001% to 6%; 0.001% to 5%; 0.001% to 3%; 0.001% to 2%; 0.05% to 2%; 0.1% to 2% or 0.1% to 0.9%. In the present invention, since the cross-section of the positive electrode mixture layer has a structure in which the second region is uniformly dispersed in the first region at a specific area ratio after initial charging (activation), the generation of side reactions and / or gases such as oxygen (O2) caused by the positive electrode additive during charging / discharging after activation can be minimized or prevented.
[0087] Furthermore, the crack structure formed in the second region may have a needle-like structure having an average thickness of 5 nm to 800 nm and an average length of 50 nm to 10 μm.
[0088] Specifically, the average thickness of the needle cracks can be 5 to 700nm; 5 to 250nm; 5 to 100nm; 5 to 50nm; 5 to 25nm; 10 to 30nm; 15 to 60nm; 50 to 200nm; 80 to 250nm; 100 to 300nm; 150 to 300nm; 200 to 400nm; 250 to 500nm or 500 to 800nm.
[0089] In addition, the average length of the needle cracks can be 50nm to 8μm; 50nm to 6μm; 50nm to 5μm; 50nm to 3μm; 50nm to 2μm; 50nm to 1μm; 50 to 900nm; 50 to 750nm; 50 to 500nm; 50 to 250nm; 100 to 500nm; 100 to 900nm; 200 to 400nm; 500 to 900nm; 900nm to 2μm; 1 to 10μm; 1 to 8μm; 1 to 5μm; 1 to 3μm; 5 to 10μm; 2 to 6μm; 4 to 7μm; 1 to 3μm; 2 to 4μm; or 0.8μm to 1.2μm.
[0090] Here, the average length may refer to the length of the major axis, which is the longest line segment of a straight line passing through the center of the crack and a line segment with the center as the intersection point; and the average thickness may refer to the length of the minor axis, which is the shortest line segment of a line orthogonal to the major axis and passing through the center of the crack and a line segment with the center as the intersection point. In addition, the needle crack may be connected to adjacent needle cracks to form a single line shape (e.g., a straight line or a curve), and as the line shape is repeated, a crack structure including ridges and valleys may be randomly formed.
[0091] In one example, the second region may include needle-shaped cracks having an average thickness of 10 nm to 100 nm and an average length of 300 nm to 1 μm.
[0092] In another example, the second region may include needle cracks having an average thickness of 400 nm to 700 nm and an average length of 2 μm to 7 μm.
[0093] In still another example, the second region may have a structure in which first needle cracks having an average thickness of 10 nm to 100 nm and an average length of 300 nm to 1 μm and second needle cracks having an average thickness of 400 nm to 700 nm and an average length of 2 nm to 7 μm are mixed.
[0094] In yet another example, the second region may include a needle-like structure having an average thickness of 50 nm to 90 nm and an average length of 500 nm to 1,500 nm, and the needle-like structure may be irregularly disposed and connected.
[0095] In addition, the crack structure formed in the second region may include a plurality of needle-shaped cracks, and the needle-shaped cracks may be formed irregularly; in some cases, the cracks may be oriented in one direction or based on one point to form a radial shape; or may be connected to form an irregular network structure, but the present invention is not limited thereto.
[0096] In the present invention, by controlling the shape and size of cracks formed in the second region, side reactions and / or gases such as oxygen (O2) generated by the positive electrode additive represented by Formula 1 can be improved during charge / discharge after initial charge (activation).
[0097] In addition, the shape or size of the crack structure formed in the second region can control the initial charging conditions of the lithium secondary battery, that is, the activation conditions. Specifically, the crack structure in the second region can be formed by activating the lithium secondary battery under a constant current condition of 0.6 to 50 mA; or in some cases, it can be formed under a constant current-constant voltage condition with a final charging voltage of 4.2 V or less and 1.0 C or less, and activation can be performed in stages according to SOC.
[0098] For example, the crack structure of the second region can be achieved by continuously performing a three-step charging process, that is, 1 to 3 steps of activation in the initial charging of the positive electrode for the lithium secondary battery. Specifically, the initial charging can be performed in three steps: a first step of activation for charging the lithium secondary battery to a SOC of 30% or more and less than 40% by applying a current of 0.05C to 0.3C; a second step of activation for charging the lithium secondary battery that has undergone the first step of activation to a SOC of 40% or more and less than 50% by applying a current of 0.3C to 0.5C; and a third step of activation for charging the lithium secondary battery that has undergone the second step of activation to a SOC of 50% or more and less than 60% by applying a current of 0.6C to 0.9C.
[0099] In one example, the crack structure of the second region can be formed by performing three steps: a first activation step for charging the lithium secondary battery to a SOC of 30% to 39% by applying a current of 0.08C to 0.15C during initial charging; a second activation step for charging the lithium secondary battery that has undergone the first activation to a SOC of 40% to 49% by applying a current of 0.35C to 0.45C; and a third activation step for charging the lithium secondary battery that has undergone the second activation to a SOC of 50% to 59% by applying a current of 0.65C to 0.8C.
[0100] On the other hand, the positive electrode mixture layer may further contain a conductive material, a binder, or an additive in addition to the positive electrode active material and the positive electrode additive.
[0101] Here, the conductive material can be used to improve the performance of the positive electrode, such as conductivity, and can include one or more selected from the following: natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon nanotubes, graphene and carbon fiber. For example, the conductive material can include acetylene black.
[0102] In addition, relative to 100 parts by weight of the positive electrode mixture layer, the content of the conductive material can be 0.5 to 5 parts by weight, specifically 0.5 to 4 parts by weight; 0.5 to 3 parts by weight; 0.5 to 1 part by weight; 0.5 to 2 parts by weight; 1 to 3 parts by weight; 2 to 4 parts by weight; 1.5 to 3.5 parts by weight; 0.5 to 1.5 parts by weight; or 1 to 2 parts by weight.
[0103] In addition, the binder may include one or more resins selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVdF-co-HFP), polyvinylidene fluoride (PVdF), polyacrylonitrile, polymethyl methacrylate and copolymers thereof. In one example, the binder may include polyvinylidene fluoride.
[0104] In addition, the content of the binder may be 1 to 10 parts by weight, specifically 2 to 8 parts by weight; or 1 to 5 parts by weight, relative to 100 parts by weight in total of the positive electrode mixture layer.
[0105] Furthermore, the average thickness of the positive electrode mixture layer may be specifically, but not particularly limited to, 50 to 300 μm, more specifically 100 to 200 μm; 80 to 150 μm; 120 to 170 μm; 150 to 300 μm; 200 to 300 μm; or 150 to 190 μm.
[0106] In addition, in the positive electrode, a positive electrode current collector having high conductivity and not causing chemical changes in the battery can be used as a positive electrode current collector. For example, as a positive electrode current collector, stainless steel, aluminum, nickel, titanium or sintered carbon can be used, and in the case of aluminum or stainless steel, aluminum or stainless steel treated with carbon, nickel, titanium or silver surface can also be used. In addition, the positive electrode current collector may have fine concave-convex formed on its surface to increase adhesion to the positive electrode active material, and may be formed in various forms such as films, sheets, foils, nets, porous bodies, foams and non-woven fabrics. In addition, considering the conductivity and total thickness of the positive electrode to be manufactured, the average thickness of the current collector can be appropriately applied in the range of 3 μm to 500 μm.
[0107] Lithium secondary battery
[0108] In addition, in one embodiment of the present invention, there is provided a lithium secondary battery comprising the positive electrode according to the present invention described above, a negative electrode, and a separator interposed between the positive electrode and the negative electrode.
[0109] The lithium secondary battery according to the present invention comprises the positive electrode of the present invention described above, and thus can exhibit excellent characteristics such as battery safety and electrical performance. The lithium secondary battery of the present invention has a structure comprising the positive electrode described above; a negative electrode; and a separator inserted between the positive electrode and the negative electrode.
[0110] Here, for the negative electrode, a negative electrode mixture layer is formed by coating, drying and pressing a negative electrode active material on a negative electrode collector, and like the positive electrode, the negative electrode may further selectively contain a conductive material, an organic binder polymer or an additive as needed.
[0111] In addition, the negative electrode active material may include, for example, a carbon material and a silicon material. Carbon material refers to a carbon material containing carbon atoms as a main component, and examples of carbon materials may include: graphite such as natural graphite with a complete layered crystal structure, soft carbon with a low crystalline layered crystal structure (graphene structure; a structure in which the hexagonal honeycomb planes of carbon are arranged in layers) and hard carbon in which the above structure is mixed with an amorphous part, artificial graphite, expanded graphite, carbon nanofibers, non-graphitized carbon, carbon black, acetylene black, Ketjen black, carbon nanotubes, fullerenes, activated carbon and graphene, preferably one or more selected from the following: natural graphite, artificial graphite, graphene and carbon nanotubes. More preferably, the carbon material includes natural graphite and / or artificial graphite, and may also include any one or more of graphene and carbon nanotubes in addition to natural graphite and / or artificial graphite. In this case, the carbon material may include 50 to 95 parts by weight, more specifically 60 to 90 parts by weight or 70 to 80 parts by weight of the graphene and / or the carbon nanotube, relative to a total of 100 parts by weight of the carbon material.
[0112] In addition, the silicon material is a particle containing silicon (Si) as a metal component as a main component, and may contain silicon (Si) particles and silicon oxide (SiO X , 1≤X≤2) particles. In one example, the silicon material may include silicon (Si) particles, silicon monoxide (SiO) particles, silicon dioxide (SiO2) particles, or a mixture thereof.
[0113] In addition, the silicon material may have a form in which crystalline particles and amorphous particles are mixed, and the proportion of the amorphous particles may be 50 to 100 parts by weight, specifically 50 to 90 parts by weight, 60 to 80 parts by weight, or 85 to 100 parts by weight based on 100 parts by weight of the entire silicon material. In the present invention, by controlling the proportion of amorphous particles included in the silicon material within the above range, thermal stability and flexibility can be improved without reducing the electrical properties of the electrode.
[0114] In addition, the negative electrode active material contains a carbon material and a silicon material, and based on 100 parts by weight of the negative electrode mixture layer, may include 1 to 20 parts by weight, in particular 5 to 20 parts by weight; 3 to 10 parts by weight; 8 to 15 parts by weight; 13 to 18 parts by weight; or 2 to 7 parts by weight.
[0115] In the present invention, by adjusting the contents of the carbon material and the silicon material contained in the negative electrode active material to within the above range, the lithium consumption and irreversible capacity loss during the initial charge / discharge of the battery can be reduced, and the charge capacity per unit mass can also be improved.
[0116] In one example, the negative electrode active material may include 95±2 parts by weight of graphite and 5±2 parts by weight of a mixture in which silicon monoxide (SiO) particles and silicon dioxide (SiO2) particles are uniformly mixed, relative to 100 parts by weight of the negative electrode mixture layer. In the present invention, by adjusting the contents of the carbon material and the silicon material contained in the negative electrode active material to within the above range, the lithium consumption and irreversible capacity loss during the initial charge / discharge of the battery can be reduced, and the charge capacity per unit mass can also be improved.
[0117] In addition, the average thickness of the negative electrode mixture layer may be 100 to 200 μm, specifically 100 to 180 μm, 100 to 150 μm, 120 to 200 μm, 140 to 200 μm, or 140 to 160 μm.
[0118] In addition, there is no particular restriction on the negative electrode collector, as long as it does not cause chemical changes in the battery and has high conductivity, for example, copper, stainless steel, nickel, titanium or sintered carbon can be used, and in the case of copper or stainless steel, copper or stainless steel whose surface has been treated with carbon, nickel, titanium or silver can be used. In addition, like the positive electrode collector, the negative electrode collector also has fine concave-convex on its surface, thereby enhancing the adhesion with the negative electrode active material, and can be formed in various shapes such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics. In addition, considering the conductivity and total thickness of the negative electrode to be formed, the average thickness of the negative electrode collector can be appropriately applied within 3 to 500 μm.
[0119] In addition, as a separator, an insulating film is used, which is inserted between the positive electrode and the negative electrode and has high ion permeability and mechanical strength. There is no particular limitation on the separator, as long as it is commonly used in the art, specifically, a sheet or non-woven fabric made of chemically resistant and hydrophobic polypropylene, glass fiber or polyethylene can be used. In some cases, a composite separator can be used, in which a porous polymer substrate such as a sheet or a non-woven fabric is coated with an organic binder polymer and inorganic / organic particles. When a solid electrolyte such as a polymer is used as an electrolyte, the solid electrolyte can also act as a separator. In addition, the pore size of the separator can be an average of 0.01 to 10 μm and the thickness can be an average of 5 to 300 μm.
[0120] On the other hand, the positive electrode and the negative electrode may be wound in a roll shape and accommodated in a cylindrical, prismatic, or pouch-type battery, or may be accommodated in a pouch-type battery in a folded or stacked and folded form, but the present invention is not limited thereto.
[0121] Furthermore, the lithium salt-containing electrolyte according to the present invention may be composed of an electrolyte and a lithium salt, and as the electrolyte, a nonaqueous organic solvent, an organic solid electrolyte, or an inorganic solid electrolyte may be used.
[0122] As the nonaqueous organic solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate and ethyl propionate can be used.
[0123] As the organic solid electrolyte, for example, polymers such as polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate polymers, polyalginate-lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, and polymers containing ion dissociative groups can be used.
[0124] As an inorganic solid electrolyte, for example, a nitride, halide or sulfate of Li can be used, such as Li3N, LiI, Li5Ni2, Li3N-LiI-LiOH, LiSiO4, LiSiO4-LiI-LiOH, Li2SiS3, Li4SiO4, Li4SiO4-LiI-LiOH or Li3PO4-Li2S-SiS2.
[0125] Lithium salts are materials that are easily soluble in non-aqueous electrolytes, such as LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, (CF3SO2)2NLi, lithium chloroborane, lithium lower aliphatic carboxylate, lithium tetraphenylborate or lithium imide.
[0126] In addition, in order to improve the charge / discharge characteristics and flame retardancy, for example, the following may be added to the electrolyte: pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, glycol dimethyl ethers, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N, N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum chloride. In some cases, in order to impart non-flammability, a halogen-containing solvent such as carbon tetrachloride or ethylene trifluoride may be further included, and in order to enhance high temperature storage performance, carbon dioxide gas may be further included, and fluoroethylene carbonate (FEC) or propene sultone (PRS) may also be included.
[0127] [Example]
[0128] Hereinafter, the present invention will be described in further detail with reference to Examples and Experimental Examples.
[0129] However, the following Examples and Experimental Examples merely illustrate the present invention, and the contents of the present invention are not limited to the following Examples and Experimental Examples.
[0130] Manufacturing of Lithium Secondary Batteries of Examples 1 to 3 and Comparative Examples 1 to 4
[0131] a) Manufacturing of positive electrodes for lithium secondary batteries
[0132] The positive electrode slurry for lithium secondary battery was prepared by injecting N-methylpyrrolidone into a homogenizer, weighing and adding 97 parts by weight of positive electrode active material LiNi with respect to 100 parts by weight of the solid content of the positive electrode slurry. 0.6 Co 0.2 Mn 0.2 O2, 0.8 parts by weight of positive electrode additive Li6CoO4 or Li6Co 0.7 Zn 0.3 O4; 0.7 parts by weight of a conductive material, which is a mixture of carbon nanotubes (average size: 60±10nm) and Danka black (average size: 2±0.5μm) (75:25 weight / weight); and 1.5 parts by weight of a binder PVdF, and the resultant is mixed at 2,000rpm for 60 minutes. The positive electrode is manufactured by applying the prepared positive electrode slurry to one surface of the aluminum current collector, drying the slurry at 100°C, and rolling the resultant. Here, the total thickness of the positive electrode mixture layer is 130μm, and the total thickness of the manufactured positive electrode is about 200μm.
[0133] b) Manufacturing of lithium secondary batteries
[0134] Relative to 100 parts by weight of the solid content of the negative electrode slurry, 84 parts by weight of natural graphite, a negative electrode active material, and 14 parts by weight of silicon (SiOx, 1≤x≤2) particles were prepared; and 2 parts by weight of a binder, styrene-butadiene rubber (SBR), and the negative electrode slurry was prepared in the same manner as the positive electrode slurry. Here, the graphite used to form the negative electrode mixture layer is natural graphite (average particle size: 0.01 to 0.5 μm), and the average particle size of the silicon (SiOx) particles is 0.9 to 1.1 μm. The negative electrode is manufactured by applying the prepared negative electrode slurry to one surface of a copper current collector, drying the slurry at 100°C, and rolling the resultant. Here, the total thickness of the negative electrode mixture layer is 150 μm, and the total thickness of the manufactured negative electrode is about 250 μm.
[0135] The battery was assembled into a full-cell type by stacking a separator (thickness: about 16 μm) composed of a porous polyethylene (PE) film inserted between the prepared positive and negative electrodes and injecting E2DVC as an electrolyte. Here, "E2DVC" refers to a carbonate electrolyte, which is a mixed solution in which lithium hexafluorophosphate (LiPF6, 1.0 M) and ethylene carbonate (VC, 2 wt%) are added to a mixture of ethylene carbonate (EC): dimethyl carbonate (DMC): diethyl carbonate (DEC) = 1:1:1 (volume ratio).
[0136] A lithium secondary battery was manufactured by initially charging the manufactured full cell at 22±2° C. under the conditions shown in Table 1 below.
[0137] [Table 1]
[0138]
[0139] Experimental example
[0140] In order to evaluate the performance of the positive electrode for a secondary battery according to the present invention, the following experiment was performed.
[0141] a) Cross-sectional structural analysis of the positive electrode mixture layer after initial charging
[0142] The samples were prepared by separating the positive electrodes from the initially charged lithium secondary batteries in Examples 1 to 3 and Comparative Examples 1 to 4 and peeling off the positive electrode mixture layer from the separated positive electrodes, and the cross sections of the respective samples prepared above were subjected to SEM analysis. Figure 1 (a) and 1(b).
[0143] According to Figure 1 The results shown in (a) and 1(b) confirm that the positive electrode mixture layer separated from the lithium secondary battery of Examples 1 to 3 has a structure in which fine needle-like cracks are formed in an island shape inside and on the surface of some metal oxides (specifically, positive electrode additive particles shown in gray) and at the interface between the positive electrode additive particles, and no cracks exist due to the dense filling of the positive electrode active material particles shown in white. Here, it is confirmed that the needle-like cracks have a structure in which the following cracks are mixed: a first crack with an average thickness of 10nm to 100nm and an average length of 150nm to 400nm; and a second crack with an average thickness of 500nm to 750nm and an average length of 5.5μm to 7.3μm. It is confirmed that some first cracks and second cracks are irregularly connected to form a line shape (e.g., a straight line or a curve). In addition, it is seen that the crack structure accounts for 0.5% to 5% of the total cross-sectional area.
[0144] On the contrary, it was confirmed that the positive electrode mixture layer separated from the lithium secondary batteries of Comparative Examples 1 to 4 had a crack structure over the entire cross section of the mixture layer, or had a structure in which a region having a crack structure formed in an island shape in the positive electrode additive particles, as in the positive electrode mixture layer of the embodiment. However, it was confirmed that the average thickness and average length of the cracks formed were significantly greater than those of the embodiment, and the cracks occupied more than 10% of the total cross-sectional area of the mixture layer.
[0145] As can be seen from the above results, in the positive electrode for a lithium secondary battery according to the present invention, cracks formed in the positive electrode mixture layer can be controlled during the activation process.
[0146] b) Evaluation of the cumulative amount of gas generated during charge / discharge after initial charge
[0147] After degassing the initially charged lithium secondary batteries of Examples 1 to 3 and Comparative Examples 1 to 4, the lithium secondary batteries were discharged to a final voltage of 2V at a discharge current of 0.1C, and the secondary batteries from which the internal gas was removed were repeatedly charged / discharged 50 times at 45°C under the conditions of 4.5V and 1.0C. Here, the cumulative amount of gas generated after the initial charge / discharge was measured by measuring the amount of gas generated in each charge / discharge. The results are shown in Table 2 below.
[0148] c) Cycle life performance evaluation
[0149] The initially charged lithium secondary batteries of Examples 1 to 3 and Comparative Examples 1 to 4 were subjected to degassing treatment, the batteries were discharged at a discharge current of 0.1C until a final voltage of 2V, and then the batteries were subjected to 100 charge / discharge cycles (n=100) at 25°C, a charge final voltage of 4.25V, a discharge final voltage of 2.5V, and 0.5C / 0.5C, and then the capacity retention rate [%] was measured. Here, the capacity retention rate was calculated using the following equation 1, and the results are shown in the following Table 2.
[0150] [Equation 1]
[0151] Capacity retention rate (%) = (discharge capacity after 100 charge / discharge cycles / discharge capacity after initial charge / discharge cycles) × 100
[0152] [Table 2]
[0153]
[0154] As shown in Table 2, the positive electrode for the lithium secondary battery according to the present invention contains the positive electrode additive represented by Formula 1, and also has a configuration in which a specific crack structure is introduced into the cross section of the positive electrode mixture layer after initial charge, so that it can be seen that the safety and electrical performance of the lithium secondary battery are excellent.
[0155] Specifically, it was confirmed that in the lithium secondary battery manufactured in the embodiment, the amount of gas generated in the initial charge / discharge was significantly reduced after the gas generated in the initial charge / discharge was degassed. In addition, it was confirmed that the lithium secondary battery had a high initial charge capacity of more than 103 mAh and a high capacity retention rate of more than 95%.
[0156] On the other hand, in the lithium secondary battery manufactured in the comparative example, a large amount of gas is generated by promoting the decomposition of the electrolyte during the charge / discharge period after the initial charge (activation). In addition, it is confirmed that the lithium secondary battery of the comparative example shows a low initial charge capacity of less than 102mAh due to the decomposition of the electrolyte, and a capacity retention rate of less than 94% after 100 charge / discharge cycles.
[0157] According to the above results, since the positive electrode for a lithium secondary battery contains the positive electrode additive represented by Formula 1 and has a positive electrode mixture layer containing a region having a needle-like crack structure in its cross section after initial charge (activation), the amount of gas such as oxygen generated by the irreversible additive as a positive electrode additive is reduced during charge / discharge after the initial charge, and the migration path of lithium ions and / or electrons can be ensured, thereby achieving an excellent effect of improving the battery safety and electrical performance of the lithium secondary battery.
[0158] Hereinabove, the present invention has been described with reference to exemplary embodiments, but those skilled in the art or ordinary technicians in the field should understand that various modifications and changes can be made to the present invention without departing from the spirit and technical scope of the invention described in the appended claims.
[0159] Therefore, the technical scope of the present invention is not limited to the contents described in the specific embodiments of the specification, but should be defined by the claims.
Claims
1. A positive electrode for a lithium secondary battery, the positive electrode comprising: a positive electrode current collector, and A positive electrode mixture layer is provided on at least one surface of the positive electrode current collector and includes a positive electrode active material and a positive electrode additive represented by the following Formula 1, in, After initial charging, the cross-sectional structure of the positive electrode mixture layer comprises: a first region having a dense structure filled with first metal oxide particles, and a second region having a needle-like crack structure inside and outside the second metal oxide particle, wherein the second region accounts for 0.001% to 10% of the total cross-sectional area of the positive electrode mixture layer, [Formula 1] Li p Co (1-q) M 1 q O4 In formula 1, M 1 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, and p and q are 5≤p≤7 and 0≤q≤0.5 respectively.
2. The positive electrode according to claim 1, wherein The second region has a structure dispersed in the first region in an island shape.
3. The positive electrode according to claim 1, wherein The needle-like crack structure has cracks having an average thickness of 5 nm to 800 nm and an average length of 50 nm to 10 μm. The positive electrode according to claim 1 , wherein the positive electrode additive has a tetragonal structure with a space group of P42 / nmc.
5. The positive electrode according to claim 1, wherein the positive electrode active material is a lithium metal composite oxide represented by the following formula 2: [Formula 2] Li x [Ni y Co z Mr w M 2 v ]O u In formula 2, M 2 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, and x, y, z, w, v and u are 1.0≤x≤1.30, 0.1≤y<0.95, 0.01 respectively <z≤0.5、0.01<w≤0.5、0≤v≤0.2、1.5≤u≤4.5。 6. The positive electrode according to claim 1, wherein The positive electrode mixture layer further includes one or more conductive materials selected from the group consisting of natural graphite, artificial graphite, carbon black, and carbon fiber.
7. A lithium secondary battery, comprising: The positive electrode according to claim 1, negative electrode, and A separator is disposed between the positive electrode and the negative electrode.
8. The battery according to claim 7, wherein The negative electrode comprises: a negative electrode current collector; and a negative electrode mixture layer provided on at least one surface of the negative electrode current collector and containing a negative electrode active material, The negative electrode active material contains a carbon material and a silicon material.
9. The battery according to claim 8, wherein The silicon material comprises silicon Si particles and silicon oxide SiO X One or more of particles, where 1≤X≤2.
10. The battery according to claim 8, wherein The silicon material may be contained in an amount of 1 part by weight to 20 parts by weight relative to 100 parts by weight of the negative electrode mixture layer.
11. The battery according to claim 8, wherein The carbon material comprises one or more selected from the group consisting of natural graphite, artificial graphite, carbon black, carbon fiber, graphene and carbon nanotube.
Citation Information
Patent Citations
Additives for positive electrode, method for manufacturing the same, positive electrode including the same, and lithium recharegable battery including the same
KR1020190078392A
High strength steel plate for sour-resistant line pipe and method for manufacturing same, and high strength steel pipe using high strength steel plate for sour-resistant line pipe
KR1020210064296A
Nitride piezoelectric material and MEMS device using the same
KR1020220016953A
KR20190124038A